“TEACHING IS ASTONISHINGLY FULFILLING” A QUALITATIVE STUDY ON JOB SATISFACTION IN BIREUEN REGENCY, ACEH - Fajrinur, Fajrinur; Bella, Ivvon Septina; Sylvia, Rizka (Jurnal Review Pendidikan dan Pengajaran, 2024)
This qualitative study focused on understanding job satisfaction from three teachers in Bireuen Regency, Aceh. Data collected through interviews were analysed using a framework of four categories:, their beliefs on their ways of teaching, teachers’ reasons to take teaching carrier, things they criticize  and things that make them happy in teaching, and whether they find teaching is fulfilling. The interview result showed that the three teachers love of their job. The teacher believes in, not only teaching the content knowledge but also “akhlak” and personality as a focus of their teaching. The three teachers interviewed perceived that their intentions to choose teaching carrier are not sincere, since they did not plan to be teacher or because teaching is their ambition, but the salary factor and economical factor may influence their decision, but the interview result indicated that once the teachers face their students, they are doing their best to teach them and at the same time to shape their personality. The teachers realized that there a things need to be fixed in their teaching and have definitely things they love in teaching. In term of job satisfaction, the three teachers are satisfied with their job. Mrs. R stated “teaching is astonishingly fulfilling”, while the other two teachers expressed their satisfaction in similar manner.